Comparison of Two Bovine Commercial Xenografts in the Regeneration of Critical Cranial Defects - Zapata-Ramirez, P; Saavedra-Gonzalez, M (Multidisciplinary Digital Publishing Institute (MDPI), 2022)
Autologous bone is the gold standard in regeneration processes. However, there is an endless search for alternative materials in bone regeneration. Xenografts can act as bone substitutes given the difficulty of obtaining bone tissue from patients and before the limitations in the availability of homologous tissue donors. Bone neoformation was studied in critical-size defects created in the parietal bone of 40 adult male Wistar rats, implanted with xenografts composed of particulate bovine hydroxyapatite (HA) and with blocks of bovine hydroxyapatite (HA) and Collagen, which introduces crystallinity to the materials. The Fourier-transform infrared spectroscopy (FTIR) analysis demonstrated the carbonate and phosphate groups of the hydroxyapatite and the amide groups of the collagen structure, while the thermal transitions for HA and HA/collagen composites established mainly dehydration endothermal processes, which increased (from 79 °C to 83 °C) for F2 due to the collagen presence. The xenograft’s X-ray powder diffraction (XRD) analysis also revealed the bovine HA crystalline structure, with a prominent peak centered at 32°. We observed macroporosity and mesoporosity in the xenografts from the morphology studies with heterogeneous distribution. The two xenografts induced neoformation in defects of critical size. Histological, histochemical, and scanning electron microscopy (SEM) analyses were performed 30, 60, and 90 days after implantation. The empty defects showed signs of neoformation lower than 30% in the three periods, while the defects implanted with the material showed partial regeneration. InterOss Collagen material temporarily induced osteon formation during the healing process. The results presented here are promising for bone regeneration, demonstrating a beneficial impact in the biomedical field. © 2022 by the authors.